2020
DOI: 10.1001/jamadermatol.2019.3844
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patch Test Findings in Patients With Anogenital Dermatitis

Abstract: IMPORTANCEContact dermatitis in the anogenital area is associated with sleep disturbance and dyspareunia and can profoundly affect quality of life. The literature on anogenital contact dermatitis and culprit allergens is limited. The last large-scale study on common, relevant allergens in patients with anogenital dermatitis was published in 2008.OBJECTIVES To characterize patients with anogenital dermatitis referred for patch testing by the North American Contact Dermatitis Group, to identify common allergens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
0
21
1
Order By: Relevance
“…The ratio of men to women with ACD from topical drugs applied onto the anal/genital area was not significantly different from the ratio in the total population tested, that is, more women than men were affected. This differs from the results from a recent study from the United States about patch test results in patients with anogenital dermatitis, 9 in which a higher number of men were involved. However, the authors also took cosmetics into account, in which isothiazolinone preservatives are used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The ratio of men to women with ACD from topical drugs applied onto the anal/genital area was not significantly different from the ratio in the total population tested, that is, more women than men were affected. This differs from the results from a recent study from the United States about patch test results in patients with anogenital dermatitis, 9 in which a higher number of men were involved. However, the authors also took cosmetics into account, in which isothiazolinone preservatives are used.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the allergens identified in topical medication, active principles, mainly corticosteroids and local anaesthetics, which was similar to that described in the United States, 9 were more often involved than vehicle components (Table 1). Regarding corticosteroids, reactions to budesonide and tixocortol pivalate reflect their presence in the baseline test series as contact allergy markers for, for example, amcinonide and hydrocortisone, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…Here, medication-positive patients were 2.3 times more likely to have anal/genital dermatitis as compared with medication-negative patients (95% CI, 2.02–2.60; P ≤ 0.0001). A recent study by our group characterizing anogenital dermatitis found that topical anesthetics (dibucaine, benzocaine, lidocaine) and corticosteroids (budesonide, triamcinolone) were significantly more likely positive in patients with anogenital dermatitis 14 . Many vaginal and hemorrhoidal medications contain anesthetics and topical corticosteroids.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study by our group characterizing anogenital dermatitis found that topical anesthetics (dibucaine, benzocaine, lidocaine) and corticosteroids (budesonide, triamcinolone) were significantly more likely positive in patients with anogenital dermatitis. 14 Many vaginal and hemorrhoidal medications contain anesthetics and topical corticosteroids. Nearly half (9/20) of the 20 best-selling hemorrhoid pain relief products on Amazon include an anesthetic.…”
Section: Demographicsmentioning
confidence: 99%
“…Dear Editor, Anogenital dermatitis is an underreported and underdiagnosed inflammatory skin disease that affects both women and men. 1,2 Allergic contact dermatitis (ACD) affecting the anogenital area is more likely to be developed in skin that was previously injured or exposed to several allergens and irritants. 2,3 We aimed to provide data from a Portuguese tertiary referral center regarding this overlooked condition that is associated with impaired quality of life.…”
mentioning
confidence: 99%